Estudio de factibilidad para la creación de una empresa dedicada a la renta de motocicletas y servicios moto turísticos en la ciudad de Pereira Risaralda (2013)
According to preliminary investigations conducted through secondary sources such as Internet, National Tax and Customs Office (DIAN) and Chamber of Commerce of Pereira Risaralda, it was established that in this town there are Companies that rent Motorcycles Motorcycle rides and in this sense it can be said that this sector has not been developed. By means of this Feasibility Study is to explore the possibility of offering the community and the Coffee Pereira Risaralda (Colombia), a practical, efficient and economical transport where people can save time, moving from a practical and rapidly in and out of town. In this context, it is clear that then develop the theoretical and methodological issues arising from the theory of project development, which will help to understand the impact of the product/service you are trying to position through market research, technical, organizational and financial. The type of business is determined according to the laws in force, also set the organizational structure, roles and responsibilities in the company for the development of activities that fall within the organization to create. The financial study, we estimate the required resources (own or credit) for the assembly of the company, we analyze the different economic indicators to determine the project's economic goodness, and then performed an economic evaluation of investment.